2017
DOI: 10.1016/j.biomaterials.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating hypoxic stress on pancreatic islets via in situ oxygen generating biomaterial

Abstract: A major obstacle in the survival and efficacy of tissue engineered transplants is inadequate oxygenation, whereby unsupportive oxygen tensions result in significant cellular dysfunction and death within the implant. In a previous report, we developed an innovative oxygen generating biomaterial, termed OxySite, to provide supportive in situ oxygenation to cells and prevent hypoxia-induced damage. Herein, we explored the capacity of this biomaterial to mitigate hypoxic stress in both rat and nonhuman primate pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 69 publications
(87 reference statements)
3
77
0
Order By: Relevance
“…Similarly, in our study, the benefit of silicone-CaO 2 in preventing hypoxia-induced islet damage was observed, whereas its addition in normoxic conditions may decrease ATP content and glucose-dependent insulin secretion, and seemed to increase islet oxidative stress, as shown by increased HO-1 mRNA expression. This could be linked to the high levels of ROS produced by one disk of silicone-CaO 2 , as also described for the PDMS-CaO 2 disk (Coronel, Geusz & Stabler, 2017). Indeed, partial reduction of H 2 O 2 produces free radicals, which cause oxidative stress.…”
Section: Proinflammatory and Proangiogenic State Of Encapsulated Ismentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, in our study, the benefit of silicone-CaO 2 in preventing hypoxia-induced islet damage was observed, whereas its addition in normoxic conditions may decrease ATP content and glucose-dependent insulin secretion, and seemed to increase islet oxidative stress, as shown by increased HO-1 mRNA expression. This could be linked to the high levels of ROS produced by one disk of silicone-CaO 2 , as also described for the PDMS-CaO 2 disk (Coronel, Geusz & Stabler, 2017). Indeed, partial reduction of H 2 O 2 produces free radicals, which cause oxidative stress.…”
Section: Proinflammatory and Proangiogenic State Of Encapsulated Ismentioning
confidence: 73%
“…This property could help to better buffer O 2 tension in the BAP supplied by the O 2 ‐generating biomaterial or, in the long term, by vascularization around the BAP. However, the angiogenic potential of pancreatic islets is correlated to the decrease of O 2 tension (Coronel et al, ; Vasir et al, ), and overcoming the problem of hypoxia in the BAP could delay revascularization of the graft surface. Consistently, providing O 2 through the addition of silicone‐CaO 2 reverts beneficial secretion of VEGF by NPIs cultured in a hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although, most CPO based oxygen releasing systems have used hydrophobic polymers, such as PDMS17 or polyurethane,40 we used collagen (i.e., a naturally occurring hydrophilic system), given its excellent biocompatibility and low immunogenicity 41. As collagen is a component of the ECM,9 islets that are seeded into our bioscaffold will therefore be exposed to a microenvironment similar to that of the native pancreas which, in turn, helps to maintain their function as well as regulate their cellular activities 42.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous bioscaffolds have been functionalized with exogenous growth factors (i.e., exendin‐4,14 insulin‐like growth factor‐1,14 transforming growth factor‐beta 1,15 ECM,16 vascular endothelial growth factor,8 and fibroblast growth factor‐28) to improve islet survival and function, they have not addressed the issue of providing islets with the most essential nutrient they require in the immediate post‐transplantation period—oxygen. Indeed, without any oxygen supplementation, there is substantial cellular dysfunction and death of islets within bioscaffolds as a result of low oxygen tensions 17,18. One approach to address this issue has been to use oxygen generating biomaterials (i.e., using calcium peroxide (CPO) contained within a PDMS disk—OxySite17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation